Distribuição da frequência de cepas de Mycobacterium tuberculosis multidroga resistentes (MDR) e extensivamente resistentes (XDR) do estado de São Paulo - Matsui, Tania [UNIFESP] (2020)
Tuberculosis is a disease susceptible to drug treatment, but the incorrect and irregular use of anti-tuberculosis drugs and prolonged treatment created selective conditions that promoted the emergence of resistance or multidrug resistance in isolates of Mycobacterium tuberculosis var. tuberculosis, and multidrug-resistant isolates (resistant to 1st-line drugs, isoniazid, rifampicin, pyrazinamide and ethambutol) are considered a worldwide threat. Drug resistance in M. tuberculosis var. tuberculosis usually occurs through spontaneous mutations in genes encoding the target proteins of the drugs or enzymes that activate them, so there is an interest in genotypic methods for detecting these mutations and providing rapid results in relation to traditional phenotypic methods. This study analyzed the mutations associated with resistance to 1st and/or 2nd line drugs by sequencing 156 isolates of M. tuberculosis var. tuberculosis previously characterized phenotypically by the automated system BACTEC MGIT 960 as monoresistant to isoniazid, MDR, pre-XDR and XDR in the period of 2012 to 2017 at the Adolfo Lutz Institute of São Paulo. We found that Rifampicin Resistance-Determining Region (RRDR) of the rpoB gene; codon 315 of the katG gene and the -15 region of the fabG-inhA promoter region; and Quinolone Resistance-Determining Region (QRDR) of the gyrA gene are markers for rifampin resistance; isoniazid; and fluoroquinolones, respectively and the most frequent mutations associated with resistance to these drugs identified in our study were Ser531Leu in the rpoB gene (97.3%; 109/112), Ser315Thr in the katG gene (93.9%; 108/115), Asp94Gly in the gyrA gene (44%; 18/41). A new mutation, Asp449Val, was identified in the gyrB gene and we infer that it is associated with resistance to fluoroquinolone. In relation to resistance to aminoglycosides, other gene targets should be investigated, as the analyzes on the gene target rrs were not enough to associate it with resistance to these drugs in some isolates of our work. Discordant isolates in the phenotypic and genotypic results of the 1st and 2nd line drugs were identified and in two isolates the presence of heteroresistance was observed in the fabG-inhA and gyrA promoter region. The disagreement in the other isolates can be explained by the fact that resistance to the drug is caused by mutations in other genes that were not investigated in this study or by expression of efflux pumps. The evolution of resistance from MDR to pre-XDR and/or XDR was verified in patients who had in their treatment history several re-enrollments after abandonment and/or retreatment after failure and this outcome may promote the selection of sub-populations of mycobacteria during therapy, and impairing treatment success.